Can Free Carnitine or Bilirubin in Blood Be Used in Neonatal Screening for Biliary Atresia? - Gong, Zhenhua; Wu, Yibo; Zheng, Lulu; Chen, Licai; Lv, Zhibzo (European Journal of Pediatric Surgery, 2019)
Objective To investigate the efficiency of free carnitine, unconjugated bilirubin (UBIL), bilirubin monoglucuronide (BMG), and bilirubin diglucuronide (BDG) in dry blood spots (DBSs) measured using tandem mass spectrometry (MS/MS) for screening biliary atresia (BA).Materials and Methods All the patients with BA, residing in Shanghai, were collected from four different children's hospitals in Shanghai from January 1, 2015, to June 30, 2017. UBILMS, BMG, BDG, and free carnitine were measured in the DBS samples of 48 patients with BA, 10,008 pediatric patients, and 52,862 newborns using MS/MS. Conjugated bilirubin was measured by MS/MS (CBMS) = BMG + BDG, and total bilirubin was measured by MS/MS (TBMS) = UBILMS + CBMS. Four hundred pediatric patients' direct bilirubin (DB) and total bilirubin (TB), measured by the clinical laboratory and MS/MS, were used as a control.Results The total number of births at the registered permanent residences in Shanghai was 233,000; among them, the occurrence of BA was in 33 patients in 2 years. Therefore, the incidence of BA in Shanghai was 1:7,060. The ratio of DB/TB and CBMS/TBMS of most patients with BA was elevated gradually in the neonatal period and higher than the normal range after 1 month after birth. The area under the receiver operating characteristic curve of DB, DB/TB, CBMS/TBMS, CBMS, and free carnitine for predicting BA was 0.98, 0.95, 0.73, 0.57, and 0.92, respectively. Using the 95% percentile as a cutoff, the sensitivity of DB and free carnitine to predict BA was 100 and 85%, respectively, and the specificity was 52 and 85%, respectively.Conclusion In free carnitine, DB, and CBMS/TBMS tests, blood concentrations are elevated in all infants with BA. However, they may not be elevated while they are newborns. These tests will result in high false negatives or positives. Thus, they should not be used as newborn screening tests for BA due to their lower sensitivity and specificity.
Keywords: biliary atresia; bilirubin; free carnitine; tandem mass spectrometry; neonatal screening